2022
DOI: 10.1287/mnsc.2021.4074
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity and the Tradeoff Theory of Capital Structure

Abstract: We examine the impact of ambiguity, or Knightian uncertainty, on the capital structure decision, using a static tradeoff theory model in which agents are both ambiguity and risk averse. The model confirms the well-known result that greater risk—the uncertainty over outcomes—leads firms to decrease leverage. Conversely, the model indicates that greater ambiguity—the uncertainty over the probabilities associated with the outcomes—leads firms to increase leverage. Using a theoretically based measure of ambiguity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 78 publications
2
6
1
Order By: Relevance
“…Contrary to our model,Izhakian et al (2021) shows that the optimal leverage increases in ambiguity. We find qualitatively the same result in a hypothetical case of our model in which both equity investors and debt investors price their holdings with the worst-case measure of equity investors.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our model,Izhakian et al (2021) shows that the optimal leverage increases in ambiguity. We find qualitatively the same result in a hypothetical case of our model in which both equity investors and debt investors price their holdings with the worst-case measure of equity investors.…”
contrasting
confidence: 99%
“…Our paper is closely related to several papers on optimal capital structure. Lee (2016Lee ( , 2017 and Izhakian et al (2021) also study optimal capital structure under ambiguity. However, none of them has ZL as an equilibrium outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, I show that the change in monthly ambiguity is weakly correlated with various measures of financial and economic uncertainty. This suggests that ambiguity captures a distinctly unique aspect of firm-level financial and economic uncertainty, which coincides with the comprehensive tests in recent literature (e.g., Brenner & Izhakian, 2018;Augustin & Izhakian, 2020;Izhakian et al, 2021). More precisely, previous ambiguity literature has found that various firm-level characteristics (Izhakian et al, 2021) or events (Doan et al, 2018;Ben-Rephael and Izhakian, 2020) may be related to ambiguity (distinctly from risk).…”
Section: Chapter 4: Descriptive Statisticssupporting
confidence: 86%
“…The positive correlation is to be expected, since changes in the macro-economic and political environment, which are captured by EPU, influence and change firms' information environment (Baker et al, 2016;Nagar et al, 2019). For example, uncertainty about a new regulation increases ambiguity in related firms in an industry (Izhakian et al, 2021).…”
Section: Chapter 4: Descriptive Statisticsmentioning
confidence: 99%